Office Application with Google Calendar and AI Chatbot Integration for PT Pertamina Hulu Rokan Based on Flutter - Hayuningtyas, Andina Aura; Anggara, Afwan (JISA(Jurnal Informatika dan Sains), 2025)
Effective office management is essential for improving organizational efficiency in the Industry 4.0 era. At PT Pertamina Hulu Rokan, the lack of a mobile-based system has led to fragmented data management, poor schedule coordination, and limited real-time communication, resulting in operational inefficiencies. To address these issues, this study develops a Office Application with Google Calendar and AI Chatbot Based on Flutter integration as a comprehensive digital solution to modernize office management. Flutter was chosen because it enables cross-platform development using a single codebase for both Android and iOS, reducing development time and maintenance costs while maintaining consistent performance. The system integrates Firebase for secure authentication and data management, Google Calendar API for automatic schedule synchronization, and an AI-powered chatbot for intelligent, automated communication. Developed using the Agile methodology, the application underwent iterative refinement and testing to ensure reliability and usability. The results show that the system enhances coordination, strengthens internal communication, and improves administrative efficiency. This research demonstrates that implementing Flutter with Google Calendar and AI Chatbot provides an effective, scalable approach to achieving digital transformation in large industrial organizations.